2013
DOI: 10.1213/ane.0b013e318297fcee
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Efficacy of Subcostal Transversus Abdominis Plane Block Compared with Thoracic Epidural Analgesia and Intravenous Opioid Analgesia After Radical Gastrectomy

Abstract: Single-injection subcostal TAP block was more effective than IV opioid analgesia, while continuous thoracic epidural analgesia was more effective than the single-injection subcostal TAP block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 22 publications
(11 reference statements)
2
82
2
8
Order By: Relevance
“…Only three studies [41][42][43] addressed the comparison between TAP block and epidural anesthesia, and none of them showed any significant differences between the two techniques ( Table 2). Only one RCT 43 investigated eight-hour pain score, and one trial 43 reported the 24-hr morphine consumption.…”
Section: Transversus Abdominal Plane Block Vs Epidural Analgesiamentioning
confidence: 99%
See 2 more Smart Citations
“…Only three studies [41][42][43] addressed the comparison between TAP block and epidural anesthesia, and none of them showed any significant differences between the two techniques ( Table 2). Only one RCT 43 investigated eight-hour pain score, and one trial 43 reported the 24-hr morphine consumption.…”
Section: Transversus Abdominal Plane Block Vs Epidural Analgesiamentioning
confidence: 99%
“…Only one RCT 43 investigated eight-hour pain score, and one trial 43 reported the 24-hr morphine consumption. It was not possible to perform subgroup analysis for this comparison.…”
Section: Transversus Abdominal Plane Block Vs Epidural Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…25,27,28 Subcostal TAP blocks are performed to provide analgesia in the upper quadrants of the abdominal wall. 29,30 The analgesic efficacy of TAP blocks can be prolonged by intermittent boluses or continuous infusion of local anesthetic through multihole catheters placed between the internal oblique and transversus abdominis muscle. [31][32][33] Rectus sheath blocks have also used but the evidence base is mainly for gynecologic and urologic surgery and pediatric hernias.…”
Section: Local Anesthetic Drugs Administered Peripherallymentioning
confidence: 99%
“…A recent systematic review showed the Transversus Abdominis Plane (TAP) block is safe, reduces postoperative opiate requirements, nausea/vomiting and the severity of pain after abdominal surgery [18]. It has been shown that a single-injection subcostal TAP block to be more effective than IV opioid analgesia in radical gastrectomies as Well [19]. At our center, bilateral TAP blocks are performed under ultrasound guidanceprior to surgical incision.…”
Section: Introductionmentioning
confidence: 99%